2007
DOI: 10.1261/rna.632007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of individual steps in group I intron catalysis by a peripheral metal ion

Abstract: Enzymes are complex macromolecules that catalyze chemical reactions at their active sites. Important information about catalytic interactions is commonly gathered by perturbation or mutation of active site residues that directly contact substrates. However, active sites are engaged in intricate networks of interactions within the overall structure of the macromolecule, and there is a growing body of evidence about the importance of peripheral interactions in the precise structural organization of the active si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 65 publications
8
23
0
Order By: Relevance
“…the red oxygen atom for Azoarcus residues U173 (U307) and the orange oxygen atom for Azoarcus residue G170 (A304)] and therefore seems unlikely to represent the missing M A ligand. This analysis supports the model that the effects observed upon introduction of a sulfur atom at the R P position of A304 are due to a rearrangement of the active site upon thio substitution, as described in other systems (22,(49)(50)(51) Phosphorothioate substitution at position U307R P , a position implicated in binding a peripheral metal ion referred to as M E , shifts the rescue profile to higher Cd 2+ concentrations. Possible reasons for this effect have been discussed in previous work (22).…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 84%
See 1 more Smart Citation
“…the red oxygen atom for Azoarcus residues U173 (U307) and the orange oxygen atom for Azoarcus residue G170 (A304)] and therefore seems unlikely to represent the missing M A ligand. This analysis supports the model that the effects observed upon introduction of a sulfur atom at the R P position of A304 are due to a rearrangement of the active site upon thio substitution, as described in other systems (22,(49)(50)(51) Phosphorothioate substitution at position U307R P , a position implicated in binding a peripheral metal ion referred to as M E , shifts the rescue profile to higher Cd 2+ concentrations. Possible reasons for this effect have been discussed in previous work (22).…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 84%
“…With the exception of the A304R P and the U307R P ribozymes, Cd 2+ affected the reactivity of the ribozymes less than 3-fold. The stimulatory effect on the U307R P ribozyme was previously investigated and ascribed to a peripheral metal ion, M E , that interacts with the introduced sulfur atom on the ribozyme and modulates several reaction steps (22). There was also a small stimulatory effect on the A304R P ribozyme (2.5-fold), even though the substituted oxygen atom was not implicated in functional contacts with metal ions from structural data.…”
Section: Functional Tests Detect Three Transition State Contacts Betwmentioning
confidence: 99%
“…(Adams et al 2004;Golden et al 2005;Strobel 2005, 2007) but not in those derived from crystal of the Tetrahymena group I ribozyme (Guo et al 2005), probably because of the particular truncation of the crystallized construct. The contacts between this Mg 2+ ion and the pro-R P phosphoryl oxygens of residues 307 and 308 are supported by functional studies on the Tetrahymena group I ribozyme (Forconi et al 2007). …”
Section: The 7-deaza Modification Does Not Perturb Interactions On Thmentioning
confidence: 80%
“…The Hoogsten face of guanosine is located near a cavity in the group I active site that can accommodate several water molecules (Adams et al 2004;Golden et al 2005;Stahley and Strobel 2005;Forconi et al 2007), and recent studies have suggested that deaza substitutions in nucleobases are associated with significant water and cation loss (Ganguly et al 2007(Ganguly et al , 2009(Ganguly et al , 2010.…”
Section: Duplex Stabilities Of the Analogs Correlate With The Observementioning
confidence: 99%
“…that facilitate this folding (87). It was recently shown that for the organization of the functional architecture of the Tetrahymena group I intron active site, a number of interactions, mediated by a peripheral metal ion, are important (89). This metal ion can affect differentially several steps of the catalytic process, indicating that its role is not precisely described as structural or catalytic.…”
Section: Modulation Of Group I Intron Activitymentioning
confidence: 99%